2019
DOI: 10.1039/c8ee02939c
|View full text |Cite
|
Sign up to set email alerts
|

Pt-Based electrocatalysts with high atom utilization efficiency: from nanostructures to single atoms

Abstract: This review presents recent developments in the design and synthesis of Pt-based catalysts with high atom utilization efficiency and their enhanced catalytic performance in electrochemical catalytic reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
264
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 431 publications
(267 citation statements)
references
References 157 publications
2
264
0
1
Order By: Relevance
“…
Previous works have found that the surface atomic structure and composition of catalysts play critical roles in the electrocatalytic performance of Pt-based catalysts. [5][6][7] Accordingly, nanoalloys with various atomic arrangement style including controlled composition or shape, core-shell structure, heterostructure, hollow structure and ordered structure have been designed and proved to be effective ways to modify the catalytic performance of Pt-based catalyst. [8][9][10][11][12] Furthermore, well-designed alloyed particles with Pt-enriched surfaces should possess a suitable electronic structure for ORR and thus meet both high performance and lower cost.
…”
mentioning
confidence: 99%
“…
Previous works have found that the surface atomic structure and composition of catalysts play critical roles in the electrocatalytic performance of Pt-based catalysts. [5][6][7] Accordingly, nanoalloys with various atomic arrangement style including controlled composition or shape, core-shell structure, heterostructure, hollow structure and ordered structure have been designed and proved to be effective ways to modify the catalytic performance of Pt-based catalyst. [8][9][10][11][12] Furthermore, well-designed alloyed particles with Pt-enriched surfaces should possess a suitable electronic structure for ORR and thus meet both high performance and lower cost.
…”
mentioning
confidence: 99%
“…Importantly, the photochemical transformation of sunlight into chemical energy has occurred naturally in green plants for millions of years, and is known as photosynthesis. However, sluggish reaction kinetics and the subsequent use of precious‐metal‐based catalysts to catalyze electrochemical and photochemical reactions are found to be major limitations to employing these processes on a large scale . Several materials such as metal oxides, phosphides, sulfides, chalcogenides, inorganic or organic–inorganic hybrid porous and carbon‐based materials are known in the literature separately as either electrocatalysts or photocatalysts, but purely organic‐based catalysts working as electro‐ or photocatalysts have hardly been explored …”
Section: Introductionmentioning
confidence: 99%
“…However,s luggish reactionk inetics and the subsequent use of precious-metal-based catalystst oc atalyze electrochemical and photochemical reactions are found to be majorl imitations to employing these processes on al arge scale. [16][17][18][19] Severalm aterials such as metal oxides, phosphides, sulfides, chalcogenides, inorganic or organic-inorganic hybrid porousa nd carbon-based materials are knowni nt he literature separately as either electrocatalysts [4,[20][21][22][23][24][25][26][27][28] or photocatalysts, [14,[29][30][31][32] but purely organic-based catalysts working as electro-or photocatalystshave hardly been explored. [33][34][35][36][37][38] Conjugated microporous polymers( CMPs) are an emerging class of porous organic materials, which have demonstrated a treasuret rove of applications.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, various catalysts such as noble or transition metal particles, metal phosphates/sulfides/oxides, and nonmetallic materials have been developed . Among these catalysts, noble metal (i.e., Pt, Ru, and Pd) nanoparticles show superior catalytic property due to their unfilled d orbitals and moderate Gibbs free energy of intermediates in electrocatalytic process . However, in view of the cost, transition metals (Fe, Co, and Ni)‐based catalysts with the similar unfilled d orbital that also display the good catalytic properties are promising.…”
Section: Introductionmentioning
confidence: 99%